Teachers' Difficulties in Teaching English to Young Learners in 5 Schools at Nias - Hulu, Nesti Arni (English Education Study Program STKIP PGRI Pacitan, 2024)
Teaching English to young learners is not easy as English is not their mother tongue. So teachers find it difficult to teach young learners. Therefore, the researchers conducted a study to describe the problems faced by teachers in teaching English to young learners. The purpose of this study was to find out the difficulties faced by English teachers when teaching young learners and the researchers were motivated to conduct a descriptive qualitative research on teachers' difficulties in teaching English to young learners in 5 schools in Nias. Data were collected, analyzed and interpreted using the interview method. Five English teachers were selected from different schools as participants for the interviews. The researcher used 2 weeks to conduct interviews with 5 teachers in different teaching locations. From some of the teachers' opinions, it can be concluded that there are many difficulties they encounter when teaching, namely lack of facilities, lack of knowledge in using IT, limited time, and students' lack of motivation in learning. Methods and strategies to overcome difficulties in teaching English, namely by using games, increasing vocabulary, and English songs for children.